PENGARUH CITRA TOKO, CITRA MEREK DAN LOKASI TERHADAP LOYALITAS PEMBELIAN PRODUK DI GERAI PRIA FRESHMART - Ayunanda Retno Putri; Mar’atul Fahimah (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
The emergence of covid-19 in 2019 until the present days indirectly changed the lifestyle of people in Indonesia. As a result of the covid-19, it changed people's consumption patterns. People more choose fast and easy save food. Therefore, they can still stay at home to fear the covid-19. One of the examples of fast food is frozen food. The advantages of frozen food were easy to cooking, saving, and durable. The aims of this research is to analyze the effect of brand image, store image, and location to products purchase loyalty in Prima Freshmart retail market as the company of PT Charoend Pokphand. The researcher used quantitative approach. The data analysis technique of this research used simple regression analysis. This research used purposive sampling with the consumers of Prima Freshmart Sengon Store who have been buying the product more than twice, it got 100 respondents. The results of this research showed that brand image and location of the store has significant effect on product purchase loyalty, while store image has no significant effect.